A Brief Review on Aflatoxicosis in Aquaculture With a Focus on Fish - Mina Ziarati; Ahmad Imani; Hamed Ghafarifarsani; Deepa Bhatt (Aquaculture Nutrition)
Feed quality is among the most determinative criteria for aquaculture success. Along with feed ingredient quality and its production process, feed storage conditions would also affect feed quality, especially in terms of adventitious toxins. Mycotoxins are frequent food and feed contaminants and are considered important health threats to both human and animal health. In this context, the effects of mycotoxins on aquatic animals were reviewed with an emphasis on aflatoxin B1 (AFB1), which is obviously reported in aquafeed. Severe tissue damage, increased susceptibility to infectious diseases, compromised immune system function, and increasing unknown death risks are among the most frequent symptoms of aflatoxicosis in aquatic animals. The lowest observable effect level for AFB1 has also been documented for different fish species. Considering the importance of such fungal toxins on the economic viability of aquaculture enterprises, it is recommended that further knowledge be obtained concerning the safe levels of AFB1 in terms of fish health and final product safety to human consumers.